CULTURAL SENSITIVITY IN AI TRANSLATION OF CHINESE LANGUAGE: EVALUATING AI’S CAPABILITY TO GRASP CULTURALLY RICH TEXTS - CÎNDEA, Iulia Elena; WANG, Jiong (Studia Universitatis Babeș-Bolyai Philologia, 2025)
Cultural Sensitivity in AI Translation of Chinese Language: Evaluating AI’s Capability to Grasp Culturally Rich Texts. The widespread adoption of Artificial Intelligence (AI) in translation has fundamentally reshaped global communication by enhancing efficiency, cost-effectiveness, and accessibility. Despite these advancements, critical questions persist about AI’s capacity to navigate the inherent complexities of language, particularly regarding cultural sensitivity and contextual accuracy. These challenges are especially pronounced in Chinese, a language abundant in idiomatic phrases, literary allusions, and culturally embedded references, where mistranslations risk significant misunderstanding. This study examines the capabilities of leading AI translation tools in rendering culturally rich Chinese texts into Romanian and English. Drawing on a curated corpus of classical literature, contemporary literature and news articles, the research evaluates each tool’s performance in terms of accuracy, cultural sensitivity, contextual understanding, emotional tone, and overall fluency. Both qualitative and quantitative analyses reveal considerable variation among popular platforms. While high fluency and coherence are attainable, some persistent gaps remain in the handling of idiomatic expressions and nuanced cultural elements. These findings reaffirm the need for expert post-editing and a judicious, human-centered integration of AI into translation workflows. REZUMAT. Sensibilitate culturală în traducerea asistată de IA a limbii chineze: evaluarea capacității de redare a textelor cu densitate culturală. Adoptarea pe scară largă a inteligenței artificiale (IA) în traducere a remodelat fundamental comunicarea globală, sporind eficiența, costurile și accesibilitatea. În pofida acestor progrese, persistă întrebări critice privind capacitatea IA de a gestiona complexitățile inerente ale limbajului, în special sensibilitatea culturală și acuratețea contextuală. Provocările sunt deosebit de pronunțate în chineză, limbă bogată în expresii idiomatice, aluzii literare și referințe puternic ancorate cultural, unde erorile de traducere pot genera neînțelegeri majore. Studiul de față examinează capacitățile principalelor instrumente de traducere bazate pe IA în redarea în română și engleză a textelor chineze bogate cultural. Pe baza unui corpus atent selectat, cuprinzând literatură clasică, literatură contemporană și articole de presă, cercetarea evaluează performanța fiecărui instrument în termeni de acuratețe, sensibilitate culturală, înțelegere contextuală, ton emoțional și fluență generală. Analizele calitative și cantitative evidențiază variații considerabile între platformele populare. Deși fluența și coerența ridicate sunt posibile, persistă anumite lacune în tratarea expresiilor idiomatice și a elementelor culturale nuanțate. Aceste constatări reafirmă necesitatea post-editării de către traducători profesioniști și a unei integrări cumpătate, centrate pe om, a IA în fluxurile de traducere. Cuvinte-cheie: instrumente de traducere bazate pe IA; sensibilitate culturală; hermeneutică; cultureme chineze; post-editare; traducere hibridă Article history: Received 13 June 2025; Revised 12 November 2025; Accepted 20 November 2025; Available online 12 December 2025; Available print 30 December 2025